Moral vision in the Histories of Polybius - Eckstein, Arthur M. (Berkeley : University of California Press, 1995)
Arthur Eckstein's fresh and stimulating interpretation challenges the way Polybius' Histories have long been viewed. He argues that Polybius evaluates people and events as much from a moral viewpoint as from a pragmatic, utilitarian, or even "Machiavellian" one. Polybius particularly asks for "improvement" in his audience, hoping that those who study his writings will emerge with a firm determination to live their lives nobly. Teaching by the use of moral exemplars, Polybius also tries to prove that success is not the sole standard by which human action should be judged.
Introduction: Polybius and "Machiavellianism" -- Polybius's Aristocratic Ethos: Deeds of Personal Courage -- Polybius's Aristocratic Ethos: Honor, War, and Wealth -- Polybius's Aristocratic Ethos: Deceit and Good Faith -- Threats to the Social Order in The Histories, and the Polybian Response -- The Art of Generalship as the Imposition of Order -- Politics: Greece and Rome -- Optimism and Pessimism -- Conclusion: The Duty to Act -- Appendix: Polybius on Drinking and Drunkenness.
Includes bibliographical references (pages 291-299) and indexes.
Print version record.
English.
JSTOR
Keywords: Polybius; Polybius -- Ethics; Polybius; Historiae (Polybius); Ethics, Ancient; Morale ancienne; HISTORY -- Ancient -- General; POLITICAL SCIENCE / History & Theory; Ethics; Ethics, Ancient; Historiae (Polybius); Moraal; History & Archaeology; History - General; Historiography; Roman Empire